The Effect of Education Using Media Modules on Non-Communicable Disease Control in Posbindu Cadres - Wafiatul Fuaddiyah; Sri Winarni; Dimas Dwi Yoga (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Non-communicable diseases are a major global health issue, being the leading cause of death around the world. Based on data obtained from the 2022 Malang City Office NCD pain surveillance report, 165,993 NCD cases were recorded. The incidence of NCDs arises from a combination of risk factors that cannot be combined and can be combined. The government has created a PTM Posbindu program to overcome NCDs. Objective: The purpose of this study is to determine the importance of the influence of education using module media on non-communicable disease control in posbindu cadres. Method: This study used quantitative methods with a cross sectional approach. The sampling technique in this study is total sampling, namely all posbindu cadres in the Janti Health Center work area. Result: The results showed that the knowledge of posbindu cadres before education showed that most respondents had less knowledge. Meanwhile, the knowledge of posbindu cadres after being given education shows that some respondents have good knowledge. From the results of Wilcoxon's analysis, p = 0.000 means that the p value < the value of ? (0.05) means that Ha is accepted, indicating that there is an influence of education using module media on non-communicable disease control in cadres. Conclusion: Conclusion, with this research media module proved effective as an effort to increase the knowledge of posbindu cadres.